HUBUNGAN PENGETAHUAN IBU MENYUSUI TENTANG TEKNIK MENYUSUI DENGAN PELAKSANAAN TEKNIK MENYUSUI YANG BENAR DI DESA TARAI BANGUN WILAYAH KERJA PUSKESMAS TAMBANG - Erlinawati Erlinawati (Universitas Pahlawan Tuanku Tambusai, 2017)
Breastfeeding technique is a way of feeding is done by a mother to her baby, in order to meet the nutritional needs of the infant with the attachment and positioning of mother and baby benar.Tujuan this study to determine the relationship of knowledge of mothers about breastfeeding techniques with implementing proper breastfeeding technique in the Village Tarai Build Puskesmas Mine in 2015. This study used quantitative analytical method with cross sectional study design in this study were all postpartum mothers who breastfeed in Tarai Wake Village Puskesmas Mine of the month January to July 2015.Sampel years in research This is partly postpartum mothers who breastfeed in Tarai village health centers Build working area Tambangdari months from January to July 2015 amounted to 96 orang.Teknik sample in this research is to use simple random sampling technique. Samples were taken randomly. Results of research conducted using chi-squarediperoleh value of p = 0.03 (pvalue